Sexual and reproductive health rights: comparing ethnic groups in Malaysia - Raja Ariffin, Raja Noriza; Salehud-din, Nur Intan Shaffinas; Makmor, Tumin; Zahari, Rustam Khairi (AENSI Journals, 2015)
Power works differently in different society. The norms in the cultural setting show that men play dominant and highly influential role particularly in family decision making. Although the issue of decision making in the family is crucial, the studies on this subject remain limited, particularly in Malaysia. Studies in developing countries indicated that power is perceived as control over one's partner and the ability to make decisions. Objectives: This paper explores the decision making power over women‟s sexual and reproductive health rights in Malaysia using the person who influence the decision making process as the proxy. Results: Based on the findings, generally there is not much difference between races in terms of decision making on sexual and reproductive health rights in Malaysia. Conclusion: In terms of societal settings, this study has shown that Malaysian women with the moderate societal setting, have equal right in decision making towards sexual and reproductive health issues.